STUDY OF FORM FLOOD HYDROGRAPH EFFECT TO FLOOD INUNDATION DISTRIBUTION CASE STUDY OF FLOOD PREVENTION WELANG RIVER EAST JAVA PROVINCE - Vanessa
Welang River located in East Java Province has a watershed area of 505,458 km2 with a length of the main river about 34,167 km. Every year, the downstream area of Welang River experiences flooding, but flood prevention measures are not adequate. The research was conducted to see the effect of the shape of flood hydrograph on the areal distribution of flood inundation in the Welang River. The flood hydrograph input for flood inundation simulation model was generated from Nakayasu, ITB-1, and Delmarva synthetic unit hydrograph with return periods of 2, 10, and 20 years. Simulation results show that each inflow hydrograph type will produce a very different raising and receding time as well as different flood inundation distribution. This modeling is carried out with a 1D/2D model using HEC-RAS 5.0.7 software. The boundary conditions in the upstream are filled with flood hydrograph data, while in the downstream boundary is tides elevation in MHWL, MSL, and MLWL conditions. The distribution of this flood inundation can be used for the East Java Provincial Government to be used as an illustration by the East Java Provincial Government in planning for flood management in the Welang River by looking at the distribution of floods that occur in the Welang River.